Edugamifikasi: Transformasi Pembelajaran Bahasa Indonesia dalam Keterampilan Berbahasa Siswa - Mochamad Arifin Alatas; Siti Rohmatun; Aria Indah Susanti (IAIN Madura, 2025)
Learning language skills at the junior high school level often encounters challenges, particularly low student motivation due to the continued use of conventional teaching methods. As a result, the implementation of edugamification emerges as an innovative alternative to boost student interest and improve the effectiveness of the learning process. This study aims to explore how the integration of edugamification can enhance listening, speaking, reading, and writing skills among eighth-grade students at SMP Plus Al-Ibrohimy. A qualitative approach with a case study design was employed in this research. Data were collected from both primary and secondary sources, involving Indonesian language teachers who had not previously applied edugamification, eighth-grade students actively participating in lessons, and supporting documents and materials related to this method. Thematic analysis was used to process the data, with conclusions drawn from the observed changes in edugamification-based learning. The findings revealed that the